Social support, psychological factors and substance use among early adolescents in Malaysia - Nor Hafifah Abdullah (2021)
The main objective of this study was to examine the determinants predicting substance use among early adolescents in Malaysia. The predictors were social supports (received from family, peer and school) and psychological factors (resilience and depression). This study used secondary data from the National Anti-Drug Agency (NADA) obtained from 2177 secondary school students aged 13 to 14. Data were collected from six main zones in Malaysia, which were north (Pulau Pinang and Kedah), middle (Selangor and Kuala Lumpur), south (Johor), east (Kelantan), Sabah and Sarawak. The instruments used in this study were Adolescent Concern Evaluation, Resiliency Scale and Substance Use Questionnaire. The data was analysed using binomial logistic regression analysis with an alpha level of .05. Findings showed that the significant predictors to substance use activity were social support received from school ( = -.82, Wald = .10, p = .00), resilience ( = -.60, Wald = .13, p = .00) and social support received from family ( = -.55, Wald = .13, p = .00). Thus, the obtained results revealed that a high level of resilience, social support received from school and family reduces adolescents' chances of getting involved in substance use activity. Findings from this study highlighted the importance of resilience, social support received from family and school as the protective factors against the involvement in substance use activity. Thus, it can be used to assist school management in developing suitable prevention or intervention programs to enhance adolescents' resilience in solving their behavioural problems. Future studies may investigate the influence of other factors in predicting adolescents' involvement in substance use, such as neighbourhood disadvantage, low academic achievement, anxiety and low self-esteem.